1991
DOI: 10.1111/j.1399-0004.1991.tb03060.x
|View full text |Cite
|
Sign up to set email alerts
|

Atelosteogenesis I and boomerang dysplasia: a question of nosology

Abstract: We report a patient whose clinical, radiologic and histopathologic findings are compatible with severe atelosteogenesis (AT-I). The patient is compared with previously reported cases of AT-I, as well as with patients reported as having "boomerang" dysplasia. We conclude that it is reasonable to consider AT4 and boomerang dysplasia as part of a spectrum, probably reflecting a common etiology. More and detailed clinical, radiologic and histopathologic reports are needed to further clarify the relationship of AT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The morphology of the cartilage from these patients showed acellular areas within the growth plate and the presence of large multinucleated cells (''giant cells'') ( Fig. 1D) within the resting zone as previously described [Sillence et al, 1982;Yang et al, 1983;Hunter and Carpenter, 1991].…”
Section: Clinical Phenotype Of Aoi and Aoiii Casesmentioning
confidence: 77%
“…The morphology of the cartilage from these patients showed acellular areas within the growth plate and the presence of large multinucleated cells (''giant cells'') ( Fig. 1D) within the resting zone as previously described [Sillence et al, 1982;Yang et al, 1983;Hunter and Carpenter, 1991].…”
Section: Clinical Phenotype Of Aoi and Aoiii Casesmentioning
confidence: 77%
“…In BD and AO1, the short tubular bones have been described as very short, with predominantly the middle phalanges (BD) but in severe cases also the metacarpals and proximal phalanges (AO1) unossified. Postaxial hexadactyly and partial syndactyly of the fingers have also been reported (Farrington‐Rock et al, ; Hunter & Carpenter, ; Sillence et al, ). Again, there is absolutely no ossification of the short tubular bones in POCD fetuses.…”
Section: Discussionmentioning
confidence: 92%
“…The features observed in POCD allow its classification as a distinct entity within the spectrum of giant cell osteochondrodysplasias. BD and AO1 are characterized by nonossification of all parts or of the “distal ends” of the humeri and femora, displaying a missing or seemingly global (BD) or squared and blunt (AO1) structure and associated with attenuated and shortened (in BD, bowed or boomerang like) ulnae, radii, and/or single lower leg bones, and by platyspondyly and abnormal vertebral segmentation (Farrington‐Rock et al, ; Hunter & Carpenter, ; Sillence, Worthington, Dixon, Osborn, & Kozlowski, ). However, absolutely no ossification was found in the long tubular bones and vertebrae, excluding the lateral pedicles, of our POCD fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…Review of the literature revealed 8 reports of postmortem examinations in individual cases in which the diagnosis had been confirmed by the demonstration of giant chondrocytes in cartilage [17–24]. Laryngeal stenosis had been identified in each of these cases, and hydronephrosis was also present in 1 instance [17] and the tetralogy of Fallot in another [23].…”
Section: Discussionmentioning
confidence: 99%